Investigation of The Antioxidant Activity of Cinnamon Bark Extracted with Different Solvents - Afdal, Muhammad; Kasim, Azhar; Alimon, Abdul Razak; Abdullah, Norhani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
The objective of this study was to evaluate the effect of methanol, ethyl acetate, and hexane for the extraction of cinnamon bark (Cinnamomum burmanni) (CB) on the contents of the total phenolic, total flavonoid and its 1,1,-diphonyl-1-picryl-hydrazyl (DPPH) radical scavenging activity. CB samples were ground with grinder machine in one mm sieve and extracted with treatments to determine parameter measured. All CB samples were extracted using different treatments. Parameter measured were total phenolic, total flavonoid and DPPH. CB was ground and extracted by using three treatments, data collected was statistical analysis and followed with Duncant Test, The highest total phenolic content found when CB extracted with methanol with the value of 111.43 mg gallic acids equivalent (GAE)/g DW while the lowest amount detected in hexane with the amount of 57.23 mg GAE/g dry weight (DW). It was significantly different (P<0.05) from those extracted with ethyl acetate and hexane. There was significant (P<0.05) different for the content of flavonoid among all treatment groups. Methanol was the highest solvent and hexane was the lowest with the amount of 286.27 and 64.73 mg rutin equivalent (RE)/g DW respectively. There was significantly different (P<0.05) for scavenging activity among all treatment. Using methanol in extracting CB showed the highest scavenging activity of 69.59 % among all other treatment groups. It could be concluded that Methanol was the best solution in extracting CB